The immunopeptidome of colon cancer cells treated with topoisomerase inhibiting drug reveals differential as well as common endogenous protein sampling and display of MHC I-associated peptides - Deepa Bedi; Mohammed Hassan; Alehegne Yirsaw; Biba Vikas; Pran Datta; Temesgen Samuel (Molecular & Cellular Oncology)
Immunotherapy options for microsatellite stable (MSS) colorectal cancer are currently very limited. The lack of detectably unique or altered immunogens in the tumor microenvironment may be a factor. Radiation and chemotherapy may enhance immunotherapy by increasing cancer cell visibility through Major Histocompatibility Complex I (MHC I) expression. To investigate this, we treated MSS and microsatellite-instable (MSI) colon cancer cells with a topoisomerase inhibitor and analyzed MHC I-associated peptides. Treatment increased peptide numbers by 5% in RKO (MSI) cells and 83% in SW620 (MSS) cells, with 40–50% of peptides being exclusive to treatment. Additionally, clustering analysis revealed a set of peptides with uniquely conserved residues displayed only in treated MSS SW620 cells. Gene Ontology analysis of MHC I-displayed proteins revealed a treatment-induced increase in extracellular vesicle- and nuclear-derived proteins, alongside reduced cytosolic protein sampling. Overall, we present evidence for treatment-inducible differential display of peptides, some of which may affect interactions and functions of immune cells. Given the multitude of factors that modulate the effects of increased MHC I expression and associated peptides, further studies are needed to elucidate the pathophysiological implications of these changes.